Influence of Starch Content on the Thermal and Viscoelastic Properties of Syndiotactic Polypropylene/Starch Composites - Ahmad, N.; Ahmad, F.; Alenezi, I. (Engineering, Technology & Applied Science Research, 2021)
In this study, syndiotactic Polypropylene/Starch (sPP/starch) composites were prepared using a solution mixing technique. The thermal characterization was performed using Differential Scanning Calorimetry (DSC), and the melting point was measured for all polymer composites. The thermal degradation temperature was measured using thermal gravimetric analysis. The viscoelastic measurements were performed using the Atomic Rheometric Expansion System (ARES). Both melting point and thermal degradation temperatures were found to decrease with increasing starch content. Moreover, the elastic modulus was found to decrease when the starch content increased.